(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
. The article is devoted to the problem of psychological resources, which is actively studied in modern foreign and domestic psychology. The acute relevance of the importance of its research both for theory and practice is emphasized. A theoretical review of some modern concepts of psychological resources is presented, different definitive positions regarding the interpretation of the basic concept are considered. The psychological essence of resources in the context of activity, adaptation, socially mediated and other scientific paradigms is revealed. The role of resources in the structure of resistant behavior is emphasized. An attempt is made to identify the polyvariate specificity of the phenomenon, which is mediated by a complex of vital needs. Prospects for further research are outlined.